Strategi Guru PAI dalam Mengatasi Burnout di SDN 011 Sangatta Utara - Paramita, Laura; Afandi, Nur Kholik (LP2M STAI Darul Kamal NW Kembang Kerang, 2024)
This research aims to identify and analyze the strategies used by Islamic Religious Education (PAI) teachers in overcoming burnout at SDN 011 Sangatta Utara. The method used in this research is a descriptive qualitative approach, with participants consisting of PAI teachers who teach at the school. Data was collected through in-depth interviews, observation and documentation. The research results show that burnout among PAI teachers at SDN 011 Sangatta Utara is influenced by various factors, including high workload, demands from students' parents, and lack of support from school management. Although teachers have implemented various strategies, they still face significant challenges, such as a lack of training in stress management high demands from parents and a rigid curriculum. This research concludes that to increase the effectiveness of the strategies implemented, educational institutions need to provide relevant training and adequate support for PAI teachers. It is hoped that these findings will provide insight for education stakeholders in designing better professional development programs and supporting teachers' mental well-being.